Architecture of Japanese Tea Houses: Historical Excursus - Andropova, Olga (project baikal, 2018)
The article analyzes the development of Japanese teahouse architecture as well as the aesthetic philosophy of the Way of Tea in Japanese society of those times. It describes the history of teahouse architecture formation, the main types and constructions of the buildings, the rules and peculiarities of surrounding garden landscape shaping. The turning point of Japanese tea ceremony establishment was achieved due to Sen-no-Rikyu, a tea master who outlined the aesthetics of tea ceremony, tea-house architecture of soan style, garden landscape rodji and tea utensils basing on the traditional Japanese principles of wabi (simple, natural, non-ideal beauty) and sabi (patina of the time).